Wild gentlemen and terrible savages; Hungarian travellers in Borneo in the nineteenth century - Pusztai, Gábor (UI Scholars Hub, 2024)
In the nineteenth century most of Borneo was terra incognita; an area still to be mapped. In the writings of European travellers, the indigenous people were portrayed as stereotypes. In this article, I briefly examine the representation of the indigenous in the texts of three Western European travellers: the German Karl Bernhard von Saksen-Weimar-Eisenach (1792-1862), commander of the Netherlands East Indies Army (KNIL), Ida Pfeiffer (1797-1858), an Austrian traveller, and the Norwegian traveller Carl Bock (1848-1932). I then analyse the texts of three Hungarian travellers: the traveller and scientist, János Xántus (1825-1894), the Hungarian aristocrat and author, Manó Andrássy (1821-1891), and the young Hungarian explorer, Xavér Ferenc Witti (1850-1882). The texts of the Western European travellers are compared with texts by the Hungarian writers to discover if there were such a thing as a Hungarian view of Borneo and its people. This assumption proved unfounded. Although the three texts of the three Hungarian travellers are very different from each other, they are not much different from those of contemporary Western European travellers.